Jaga Kesehatan Lansia dengan Deteksi Dini Penyakit tidak Menular sebagai Langkah Awal - AM. Al Fath Sabiliy Haq; Bella Regita Az-Zahra; Sukmawati Sukmawati; Intan Kumalasari (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Non-Communicable Diseases (NCDs) pose a growing threat to public health, especially among elderly populations. This community service program was conducted in RT 001 and RT 01A, 20 Ilir 4 Village, Palembang, focusing on early detection and education to prevent NCDs such as hypertension, diabetes, and high cholesterol. The program utilized a participatory action research approach, incorporating health screenings and interactive health education sessions. Activities included blood pressure, glucose, cholesterol measurements, and lifestyle counseling. The results demonstrated a significant increase in awareness and proactive health behaviors among residents. Over 60% of participants with high-risk conditions were referred for further medical evaluation. Regular exercise initiatives and dietary modifications were adopted by the community. The program also established health cadres trained to sustain these efforts post-intervention. This initiative highlights the effectiveness of early detection and education in reducing NCD risks and fostering long-term community health improvements.